Interactive dynamics of imagination in a science classroom - Hilppö, Jaakko Antero; Rajala, Antti; Zittoun, Tania; Kumpulainen, Kristiina; Lipponen, Lasse (Frontline Learning Research, 2016)
In this paper, we introduce a conceptual framework for researching the dynamics of imagination in science classroom interactions. While educational interest in imagination has recently increased, prior research has not adequately accounted for how imagination is realized in and through classroom interactions, nor has it created a framework for its empirical investigation. Drawing on a theory of imagination situated in cultural psychology (Zittoun et al., 2013; Zittoun & Gillespie, 2016), we propose such a framework. We illustrate our framework with a telling case (Mitchell, 1984) of imagination from a Finnish primary science classroom community. Our illustration focuses on the dynamics of imagination as it unfolds in classroom interactions and how qualitatively distinct loops of imagination are formed. In specific, we show how the students’ meaning making expands in time and space and can become more refined and differentiated through loops of imagination and their dynamics. In all, our paper argues that imagination is a constitutive element of science learning. Our proposed conceptual framework provides potential avenues for further empirical research on the dynamics of imagination in science learning and teaching.